Choroba zwyrodnieniowa stawów biodrowych - pacjent i problemy funkcjonalne = The hip joint Osteoarthritis - patient and functional problems - Piotr Biegański; Emilia Polewska (Kazimierz Wielki University, 2015)
Coxarthrosis is a chronic illness which makes destruction in the area of joint and tissues surrounding it. The hip joint Osteoarthritis is one of the most popular orthopaedic disease and second after cardiovascular disease causing disability. Patients generally feel pain and stiffness which causes decrease the possibility of locomotion, self-servive and quality of life. It is challenge for medical team to maintain efficiency as long as it is possible.